Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais (Pronat) no Território Noroeste Paulista: análise da participação dos atores sociais - Oliveira, Luciana Carvalho de [UNESP] (2014)
The process of territories' formation implemented by the Secretaria do Desenvolvimento Territorial - SDT (Territorial Development Office) of the Ministério do Desenvolvimento Agrário (Ministry of Agrarian Development) faces several obstacles regarding the different and complex realities in which they are inserted, besides operational and conceptual fragilities, resulting in a development marked by singularities in each Territory. This study had as an objective to analyze the implantation and development of Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais - Pronat (National Program of Sustainable Development of Rural Territories), in Território de Desenvolvimento do Noroeste Paulista (Northwest Development Territory of São Paulo), between 2007 and 2014, focusing on participation of institutions and social actors. Besides the literature review, the research relied on three main instruments: field notebook, documental research and semi- structured interviews. From analysis of all the information generated it was found that advances and/or difficulties since the establishment of the Territory are related, but not exclusively, with the process of the social actors' participation, because this process is also influenced by financial resources and technical support offered by the government in terms of territorial development policies. It was found that the Pronat represented an advance for the Territory-NP, to propose an institutional arrangement and a methodology that encouraged the participation of different social actors in the discussion and execution of actions, even if participation has been uneven, however, with the persistence of some actors/institutions concentrated on the Executive Committee. Finally, there are some caveats to Pronat regarding the effectiveness of their concrete result to the development of the Territory, as this suffered from interruptions in the flow of financial resources, which ...